2021
DOI: 10.3390/pharmacy9020111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an In-Person versus a Virtual Interprofessional Education Activity Focused on Professional Communication

Abstract: Early provision of interprofessional education (IPE) is imperative to ensure effective communication between healthcare professionals. However, there are several barriers to offering adequate IPE, including space restrictions and lack of human resources, prompting exploration of alternative modalities. In 2019, an IPE activity was offered in person with 213 pharmacy and 45 physician assistant (PA) students participating in one-on-one team huddles focusing on managing an acutely ill patient. In 2020, the same I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…As with other studies, our project found that the virtual format alleviated common barriers, including physical space limitations and distractions, geographical constraints, and financial costs [8,17,18]. In this study, no significant difference was noted between the intervention in 2020 and 2021, despite changes in the logistical approach utilized for each activity iteration.…”
Section: Discussionsupporting
confidence: 63%
“…As with other studies, our project found that the virtual format alleviated common barriers, including physical space limitations and distractions, geographical constraints, and financial costs [8,17,18]. In this study, no significant difference was noted between the intervention in 2020 and 2021, despite changes in the logistical approach utilized for each activity iteration.…”
Section: Discussionsupporting
confidence: 63%
“…28,29 Researchers who have examined the impact of virtual IPE concluded that virtual experiences were successful in promoting interprofessional competencies among participating students. 28,[30][31][32] The virtual platform makes it possible to bring large numbers of students from multiple health professions and different geographical locations together in a collaborative space. Even as pandemic restrictions are lifted and in-person simulations and rotations have returned to curricula nationwide, the virtual platform provides a means of curating effective interprofessional (IP) experiences.…”
Section: Virtual Ipe Researchmentioning
confidence: 99%
“…Experiences have ranged from exposure to virtual towns, online learning communities, virtual interactive patients, virtual reality, and synchronous and asynchronous group forums 28,29 . Researchers who have examined the impact of virtual IPE concluded that virtual experiences were successful in promoting interprofessional competencies among participating students 28,30–32 . The virtual platform makes it possible to bring large numbers of students from multiple health professions and different geographical locations together in a collaborative space.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual IPE often recreates the interpersonal interactions and engagement that lead to learning in the clinical workplace. 9,[23][24][25] Workplace learning theory, in particular Dornan's 'Experience-Based Learning' (ExBL) model, may therefore also be relevant. [26][27][28][29] The ExBL model details the context, process and outcome of learning in the clinical setting, describing how health professions learners engage in 'supported participation in practice' influenced by the contextual factors of interpersonal interactions and curriculum factors.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual IPE often recreates the interpersonal interactions and engagement that lead to learning in the clinical workplace 9,23–25 . Workplace learning theory, in particular Dornan's ‘Experience‐Based Learning’ (ExBL) model, may therefore also be relevant 26–29 .…”
Section: Introductionmentioning
confidence: 99%